Plant diversity and stand structure comparison of Mikania micrantha invaded and non-invaded tropical Shorea robusta forest - Basnet, S.; Chand, D. B.; Chand, D. B.; Wagle, B. H.; Wagle, B. H.; Rayamajhi, B.; Rayamajhi, B. (Banko Janakari, 2016)
Mikania micrantha is considered to be the most problematic in terrestrial ecosystem in Eastern and Central Nepal. Despite the current situation of the Mikania invasion, quantitative data on the impacts and scale of the problems are lacking for the country. Due to the lack of information regarding scale of invasion, the stakeholders have not put forwarded the proper control mechanism of the species. This paper has made an attempt to analyze the scale of invasion through the comparison of plant biodiversity and basal area per hectare as the significance of stand structure between Mikaniainvaded and non-invaded tropical Shorea robusta forest areas. This study was conducted in Barandabhar Buffer Zone Forest of Chitwan National Park. Sampling and measurement was conducted in both the invaded and non-invaded forest areas. The stand structure of both the invaded and non-invaded areas were compared in terms of different parameters like seeding density, sapling density, pole basal area per hectare and tree basal area per hectare. Statistical analysis showed that there is significant impact of Mikania on plant diversity at seedling and sapling stages. There is negative effect of Mikania on stand structure of the forest. Hence, there is urgent need to control the invasive weed so as to control further invasion and to conserve biodiversity and productivity. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 78-81, 2016